PROBLEMATIKA PEMBELAJARAN BAHASA BUGIS DI KELAS X SMA NEGERI 7 ENREKANG KABUPATEN ENREKANG - Zulqaidah, Indah; Daeng, Kembong; Asri, Aswati (Journal Studies in Indonesian Language and Literature, 2024)
The aim of this thesis research is to reveal the problems faced by teachers in learning local content of the Bugis language as well as the problems experienced by class X students in learning the Bugis language at SMA Negeri 7 Enrekang. This research is qualitative in nature and uses data collection techniques such as observation, interviews, questionnaires and documentation. The data analysis process involves three stages: data reduction, data presentation, and drawing temporary conclusions. The results of the research show that the problems of Bugis language learning faced by teachers include: (1) difficulties in creating learning tools, (2) difficulties in designing Participant Worksheets Didik (LKPD), (3) difficulties in teaching Bugis language and Lontara script, (4) difficulties in mastering teaching materials that are different from everyday language, and (5) difficulties in carrying out evaluations. The learning problems faced by students include: (1) difficulties in understanding Bugis language learning, (2) slowness in understanding lesson material, (3) lack of guidance from teachers, and (4) lack of supporting facilities such as textbooks. The solution to the problem above is to add supporting facilities for regional language learning as an effort to improve the quality of learning.